2010
DOI: 10.1007/s12522-010-0046-5
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant follicle‐stimulating hormone (follitropin alfa) versus purified urinary follicle‐stimulating hormone in a low‐dose step‐up regimen to induce ovulation in Japanese women with anti‐estrogen‐ineffective oligo‐ or anovulatory infertility: results of a single‐blind Phase III study

Abstract: Purpose We aimed to compare the efficacy and safety of recombinant human follicle-stimulating hormone (follitropin alfa) and purified urinary human follicle-stimulating hormone (urofollitropin) for ovulation induction in Japanese women with anovulatory infertility;also to verify the noninferiority (in terms of ovulation rate) of follitropin alfa versus urofollitropin. Methods In a Phase III, multicenter, single-blind, parallel-group study, we enrolled 265 Japanese women aged 20-39 years. The patients were mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The ovulation rate following a single 5000 IU dose of u‐hCG as part of an ovulation induction cycle using r‐hFSH in a low‐dose, step‐up protocol was assumed to be 95%, based on observations from two Japanese trials of r‐hFSH for ovulation induction . An ovulation rate of 95% also was observed in a global phase III trial that investigated a single 250 μg dose of r‐hCG as part of an ovulation induction cycle using r‐hFSH with a similar low‐dose, step‐up protocol…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovulation rate following a single 5000 IU dose of u‐hCG as part of an ovulation induction cycle using r‐hFSH in a low‐dose, step‐up protocol was assumed to be 95%, based on observations from two Japanese trials of r‐hFSH for ovulation induction . An ovulation rate of 95% also was observed in a global phase III trial that investigated a single 250 μg dose of r‐hCG as part of an ovulation induction cycle using r‐hFSH with a similar low‐dose, step‐up protocol…”
Section: Methodsmentioning
confidence: 99%
“…Assuming that the ovulation rate would be 95% in both arms, 72 evaluable participants (48 treated with r‐hCG and 24 with u‐hCG) were required to demonstrate that the lower limit of the two‐sided 95% CI of the difference in the ovulation rate (r‐hCG minus u‐hCG) was above the non‐inferiority margin of −20%, with at least 90% power. Allowing for a 15% cycle cancelation rate (based on the data from the trials that were used in the previous calculation), a total of 87 participants needed to be enrolled in order that 72 might be evaluable.…”
Section: Methodsmentioning
confidence: 99%
“…The phase III study of follitropin alpha was conducted adopting the starting dose of 75 IU with increment dose of 37.5 IU. Monofollicular development was achieved only in 33.3% of the patients, and the rates of hCG cancellation and OHSS were 7.0% and 7.8% . Results of the phase II and III trials suggested that 75 IU was somewhat excess as a starting dose for monofollicular development.…”
Section: Discussionmentioning
confidence: 97%
“…Monofollicular development was achieved only in 33.3% of the patients, and the rates of hCG cancellation and OHSS were 7.0% and 7.8%. 20 Results of the phase II and III trials suggested that 75 IU was somewhat excess as a starting dose for monofollicular development. Based on these data, optimized starting dose seemed to be located between 37.5 IU and 75 IU, which was a reason why we selected 50 IU and 62.5 IU as starting doses using the recent device with every 12.5 IU steps adjustable.…”
Section: Discussionmentioning
confidence: 99%
“…Ovulation induction was performed by daily injections of hMG (hMG-Kowa; Kowa Pharmaceutical Co, Tokyo, Japan) starting on day 3 of the menstrual cycle. Some of the recent patients received recombinant FSH [13]. Oocyte maturation was triggered by injecting 10,000 IU hCG (Mochida Pharmaceutical Co., Osaka, Japan).…”
Section: Ivf/icsi and Fermentioning
confidence: 99%